2016
DOI: 10.1002/rcr2.150
|View full text |Cite
|
Sign up to set email alerts
|

Primary ciliary dyskinesia with complex abnormalities including cleavage of B‐subfibers

Abstract: A 25‐year‐old Japanese woman suffered from repeated respiratory tract infections. Because of her characteristic medical history and imaging findings, we suspected primary ciliary dyskinesia (PCD) and performed a transbronchial biopsy. The biopsy revealed complex abnormalities of the ciliary structure including cleavage of the B‐subfibers observed by transmission electron microscopy analysis and the complete loss of ciliary motion by video analysis. Genetic examinations to diagnose PCD have progressed in recent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…The mean Lund-Mackay score was 12.8 (range, 7-17) points, which is comparable to the score of 10.6 (range, [6][7][8][9][10][11][12][13][14][15][16] reported in a PCD cohort [26] and to those reported in children with cystic fibrosis (17.3 for patients undergoing surgery and 11.5 for those treated medically) [27] . It has been reported that the Lund-Mackay score is not a predictor for endoscopic sinus surgery or hospitalization in PCD patients [28] .…”
Section: Article In Pressmentioning
confidence: 52%
See 2 more Smart Citations
“…The mean Lund-Mackay score was 12.8 (range, 7-17) points, which is comparable to the score of 10.6 (range, [6][7][8][9][10][11][12][13][14][15][16] reported in a PCD cohort [26] and to those reported in children with cystic fibrosis (17.3 for patients undergoing surgery and 11.5 for those treated medically) [27] . It has been reported that the Lund-Mackay score is not a predictor for endoscopic sinus surgery or hospitalization in PCD patients [28] .…”
Section: Article In Pressmentioning
confidence: 52%
“…The PICADAR score is calculated on the premise that there is wet cough, and the following seven clinical items are scored to predict the possibility of PCD: (1) full-term birth, (2) neonatal respiratory symptoms, (3) neonatal intensive care unit (NICU) admission, (4) misalignment of organs including situs inversus, (5) congenital heart disease, (6) persistent rhinitis, and (7) otitis media effusion, deafness, or perforated eardrum. Two points are assigned to (1), (2), (3), and (5), 4 points to (4), and 1 point to (6) and (7). The PICADAR score could be evaluated in 36 cases and ranged from 3 to 14 (mean, 7.3) points ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation